Usefulness of regional blocks for intubation in awake patients with difficult airway subject to general anesthesia (Boletin Médico de Postgrado, 2023)
In order to determine the usefulness of regional blocks for intubation in awake patients with difficult airway under general anesthesia who were admitted to the Hospital Central Universitario Dr. Antonio María Pineda during the period May-July 2021, a descriptive cross-sectional study was conducted, selecting a total of 32 patients which had an average age of 41.16 ± 10 years, with male sex predominance (62.5%), physical status ASA I (46.88%) and II (53.12%) and with difficult airway criteria. The main surgical pathologies were supraglottic/glottic tumor (18.75%), thyroid goiter, acute cholecystitis and clavicle fracture (15.63%, respectively). Oxygen saturation remained similar during the procedure, with no statistically significant differences, and capnography was normal after intubation. Regional blocks were performed at the level of the glossopharyngeal, superior laryngeal and transtracheal nerves, obtaining that 87.5% were effective. The average intubation time was 3.75 ± 2.39 minutes and 71.88% were successful at the first attempt. Only 3.12% of complications were reported during the procedure, mainly pain at the block site. These results show that regional blocks are a safe alternative in patients with difficult airway, with a lower risk of complications in the awake patient.
Keywords: anesthesia; airway management; intubation; nerve block; oxygen